The accounting and taxation implications on leasing in Malaysia / Noraziah Hashim - Hashim, Noraziah (1991)
When one party, called the lessee, pays another party, called the lessor, for the use of an asset, the transaction is known as a lease. Leasing on asset differs from buying an asset because the user (lessee) does not own the asset. Many firms or individuals rely heavily on leasing to acquire the use of assets. This project paper discusses the accounting and taxation implications on leasing in Malaysia environment.